An engineering methodology for constraint corrections of elastic–plastic fracture toughness – Part I: A review on probabilistic models and exploration of plastic strain effects. (January 2015) - Ruggieri, Claudio; Dodds, Robert H.
Highlights: Extensive survey of the considerable work in statistical modeling of cleavage fracture. Development of limiting distributions for fracture stress including plastic strain effects. Introduction of a modified Weibull stress incorporating plastic strain effects. Fracture resistance depends on the adopted plastic strain model. Inclusion of plastic strain effects reduces constraint corrections in toughness predictions. Abstract: This work describes a micromechanics methodology based upon a local criterion incorporating the effects of plastic strain on cleavage fracture coupled with statistics of microcracks. A parameter analysis is conducted under well-contained plasticity, where near-tip fields with varying constraint levels are generated through a modified boundary layer formulation. These analyses are extended to assess the effects of plastic strain on fracture toughness correlations for conventional SE(B) specimens with varying a / W -ratios. Fracture toughness predictions for a pressure vessel steel tested in the DBT transition region based on the proposed methodology are considered in Part II of this article.